IN VITRO EVALUATION OF ANTICANCER POTENTIAL OF ERYTHRINA VARIEGATA L. ON BREAST CANCER CELL LINES - M, Vaishali Rai; Pai, Vinitha Ramanath; Kevin, Samuel; Kedilaya, Herga P (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Species of Erythrina variegata L. is reported to be used in the treatment of cancer in traditional/folklore medicine which could be explored for their anticancer potential. We aimed to evaluate the anticancer activity of crude extracts of the leaves of E. variegata with two solvents; explore the mechanism of cytotoxicity with the effective extract and correlation with the phytochemicals in the extract. Methods: The extracts with Erythrina variegata L methanol (EVM) and chloroform (EVC) as solvents were screened for cytotoxicity by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium assay on MDA-MB-231 and MCF-7 cell lines. The effective extract was further evaluated on MDA-MB-231 cells by nucleoprotein content estimation, and cell morphology was studied. High resolution liquid chromatography mass spectrometry (HRLCMS) of EVM was done to find the phytochemical composition. Results: Among the two extracts, EVM was effective at an inhibitory concentration (IC50) value of 92 Î¼g/ml and 143 Î¼g/ml on MCF-7 and MDA-MB-231 cells, respectively. At the IC50 value (143 Î¼g/ml) the nucleoprotein content of the cells was 58.2%, and the apoptotic index was calculated to be 51.8%. EVM treated group showed significant morphological changes suggestive of apoptosis. HRLCMS revealed the presence of rutin, podocarpatriene, and cepharanthine which are known to be cytotoxic. Conclusion: This report is a contribution toward the validation of E. variegata as a potential source of anticancer agents.